Discourse, Knowledge, and Practice: Re-examining the Colombian English Language Teacher Practicum and Student-Teacher Constitution - Lucero, Edgar (Colombian Applied Linguistics Journal, 2024)
This article presents the findings of a three-stage qualitative study examining how English language teacher education in Colombia conceives its teaching practicum and student-teachers. Insights emerged from three key sources: English language student-teachers’ autoethnographies, Colombian-authored scholarly articles, and undergraduate programs’ relevant institutional documents. We analyzed each source using tailored methodologies: narrative analysis, epistemic discourse analysis, and documentary analysis. The findings reveal that the practicum is understood by three points of convergence: foundation, knowledge, and practice. This framework defines English language student-teachers by their discourse, knowledge, and practice. The study highlights that the teaching practicum is a pivotal space where student-teachers apply language education discourses and their knowledge in practice. Reflecting on how English language student-teachers are formed and how the practicum is conceived has prompted the undergraduate programs and the community to advocate for a transformation from a theoretical approach to a more flexible, experience-based approach.